P0128COMPARISON OF ULTRASTRUCTURE FEATURES BETWEEN PATIENTS WITH MERCURY-ASSOCIATED MEMBRANOUS NEPHROPATHY AND IDIOPATHIC MEMBRANOUS NEPHROPATHY. (6th June 2020) - Qin, Aibo; Lin, Zishan; Zhou, Fude; Zhao, Minghui; Wang, Suxia; Cui, Zhao
Abstract: Background and Aims: Prolonged exposure to mercury can cause membranous nephropathy. The routine clinicopathological features of mercury-associated membranous nephropathy (M-MN) and idiopathic membranous nephropathy (I-MN) are similar. The difference in ultrastructure between them was observed clinically. The current study retrospectively compared the ultrastructure features, clinical and pathological data, treatment and prognosis of patients with M-MN and I-MN. Method: Thirteen patients with M-MN and 13 patients with I-MN were enrolled. The clinical and pathological data were retrospectively collected. Electron micrographs of glomerular capillaries were taken and the foot process width (FPW) and the number of foot processes per 10 μm glomerular basement membrane (GBM) were measured. The presence and location of electron-dense deposits in mesangium and subendothelial region were recorded. Results: Patients with M-MN were younger (38.7±8.5 versus 45.8±5.7 years, P =0.020), with a shorter duration of complete remission (9.0±6.1 versus 20.3±9.8 months, P =0.004) and lower relapse rate (0% versus 45.5%, P =0.014) than patients with I-MN. As to ultrastructure, patients with M-MN had lower levels of FPW [974.3nm (range 791.2∼1504.4) versus 2370.6nm (range 2219.4∼2559.1), P =0.001, Figure 1 ], more foot processes per 10 μm GBM [8.1 (range 5.2∼10.0) versus 3.3 (range 3.1∼3.5), P =0.001], and higher ratio of mesangial electron-dense deposits (41.7% versus 0, P =0.015, Figure 2 ) than those with I-MN. Multivariate analysis showed that type of disease (M-MN or I-MN) and stage of MN (stageIor stageIIand above) were the two only determinants of FPW. FPW over 1645 nm differentiated M-MN from I-MN with high sensitivity (92.3%) and specificity (83.3%). Conclusion: The quantitative analysis of foot processes may offer a potential tool to distinguish M-MN from I-MN. Better prognosis in patients with M-MN may be related to minor podocyte damage.